The Woman who walked into doors - Doyle, Roddy, 1958- (New York, N.Y., U.S.A. : Viking, 1996)
Relates the story of Paula Spencer, a woman approaching forty and struggling with alcoholism and a violent marriage.
A novel
Keywords: Women -- Ireland -- Fiction; Ireland -- Fiction; Domestic fiction